Analisis Dinamika Proses Antara Le Minerale Dan Aqua Dalam Industri Air Mineral - Reditya Putra Octevio Rezky; Sandi Hardiansya; Syamsul Hidayat (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research aims to analyze the impact of the high demand for quality water by the community on the popularity of Bottled Drinking Water (BDW). The primary focus involves considerations of product innovation, market expansion, and consumer preferences for naturally sourced products. Additionally, the study will assess the consequences of high BDW consumption, particularly from specific brands, on plastic waste issues. Solutions in the form of green consumer behavior will also be examined as a step to address the negative environmental impact, especially in Indonesia, which faces limitations in plastic waste management. In tackling the complexity of these challenges, this research investigates the consumer purchasing decision process related to BDW, identifies factors influencing the community's need for quality water, and evaluates innovations in BDW products to meet consumer demands for instant and high-quality water. By detailing the research findings, the ultimate goal is to formulate recommendations to enhance the sustainability of BDW, including concrete steps in plastic waste management and increasing awareness of environmental issues.